2019
DOI: 10.1103/physrevb.99.195414
|View full text |Cite
|
Sign up to set email alerts
|

Drastic enhancement of the Raman intensity in few-layer InSe by uniaxial strain

Abstract: The vibrational and electronic properties of 2-dimensinal (2D) materials can be efficiently tuned by external strain due to their good stretchability. Resonant Raman spectroscopy is a versatile tool to study the physics of phonons, electrons and their interactions simultaneously, which is particularly useful for the investigation of strain effect on 2D materials. Here, for the first time, we report the resonant Raman study of strained few-layer InSe (γ-phase). Under ~ 1% of uniaxial tensile strain, one order o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 41 publications
4
45
1
Order By: Relevance
“…Four characteristic Raman peaks are observed at 115, 177, 198, and 227 cm −1 from the undoped InSe, corresponding to the A 1 ′, E′, A 2 ″, and A 1 ′ vibrational modes, respectively. [28,29,[31][32][33] After the AuCl 3 doping, the A 2 ″ peak intensity decreases, and the peak is redshifted from 198 to 191 cm −1 , while other peaks are unchanged, similar to the previous observation in the Ti 4+ -attached InSe. [28] The ratio of A 2 ″ peak to E′ peak intensity decreases from ≈2.5 to ≈1, which reveals that the electron density is reduced.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Four characteristic Raman peaks are observed at 115, 177, 198, and 227 cm −1 from the undoped InSe, corresponding to the A 1 ′, E′, A 2 ″, and A 1 ′ vibrational modes, respectively. [28,29,[31][32][33] After the AuCl 3 doping, the A 2 ″ peak intensity decreases, and the peak is redshifted from 198 to 191 cm −1 , while other peaks are unchanged, similar to the previous observation in the Ti 4+ -attached InSe. [28] The ratio of A 2 ″ peak to E′ peak intensity decreases from ≈2.5 to ≈1, which reveals that the electron density is reduced.…”
Section: Introductionsupporting
confidence: 86%
“…[28] The redshift of the A 2 ″ peak is due to the strain induced in InSe by the formation of Au NPs. [28,32] The spatial maps of the intensity ratio of the A 2 ″ peak to E′ peak (A 2 ″/E′) and the Raman shift of the A 2 ″ peak suggest that the treated surface is relatively uniform ( Figure S2, Supporting Information). The scanning electron microscope measurements further confirm the formation of NPs, which were measured as ≈33 ± 5 nm in diameter ( Figure S3, Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical calculations demonstrated that InSe monolayer can sustain a tensile strain over 20%, which is much larger than our predicted strains [20]. In the experiment, applying a strain on 2D materials are mostly through their interaction with substrates, which can be induced from heating [56], the lattice mismatch between epitaxial thin films [57], or bending of the 2D material on substrate [58, 59]. Actually, it is experimentally more common to apply uniaxial strain instead of biaxial strain.…”
Section: Resultsmentioning
confidence: 56%
“…The latter assignment is confirmed by micro‐Raman spectroscopy images (Figure S2, Supporting Information) revealing a Raman redshift of the vibrational modes A 1 ′(Γ 1 2 ) and A 1 ′(Γ 1 3 ) at the microwell edges. Tensile strain in bent InSe can shift these Raman modes [ 14,64 ] and enhance anharmonic phonon scattering, reducing phonon group velocity and heat capacity. [ 31 ] Specifically, a reduction of κ from 25.9 to 13.1 W m −1 K −1 was predicted under a strain of 6%.…”
Section: Resultsmentioning
confidence: 99%